Comparison of Positive Premarital Sexual Behavior in Kupang City High School Christian Students - Manurung, Hasanuddin; Kambey, Ellen S.; Poluan, Agnes Relly (International Journal Labs, 2023)
Positive premarital sexual behavior is basically the ability of students to carry out sexual activities before marriage such as friendship, beauty, kindness and encouragement without having a relationship before marriage. This study wanted to compare positive premarital sexual behavior in terms of psychological, social and Christian aspects. The research hypothesis that will be answered through this study is that there is a positive and significant relationship between ideal elves and premarital sexual behavior positive for Christian students of Kupang City High School. Data analyzed by simple regression analysis obtained the results of self ideal (X) correlated positively and significantly with positive premarital sexual behavior (Y) of 0.449, which means that increasing self ideal also increases positive premarital sexual behavior in Christian students of Kupang city high school. The magnitude of the coefficient of determination of 20.16%, means that the increase or decrease in positive premarital sexual behavior in Christian students of Kupang City High School by 20.16% can be explained by the number of ideal self through linear relationships whose similarities Y=51.703 + 0.765X.